WhatsApp in Brazil: mobilising voters through door-to-door and personal messages - Mauricio Moura; Melissa R. Michelson (Internet Policy Review, 2017)
Multiple randomised field experiments confirm that door-to-door canvassing and live telephone calls are effective methods of moving voters to the polls, but they require significant investments of time and resources and are difficult to bring to scale. In contrast, methods such as email, text messaging, or messages posted on social media networks are less resource-intensive and are easily expanded to large numbers of target voters. In this paper, we test the effectiveness of short candidate videos sent to eligible voters using the popular smartphone application WhatsApp. Using a set of randomised field experiments conducted during the 2014 elections in Brazil, we make two contributions to the literature. First, we find that short videos delivered via WhatsApp are a powerful method of increasing turnout among teen voters, confirming our hypothesis about how today's teens think about the networked publics in which they participate. Second, we add Brazil to the list of countries in which the traditional method of door-to-door canvassing has been proven a powerful method of mobilising voters.
Keywords: 300; WhatsApp; Micro-targeting; Turnout; Door-to-door; Mobillisation